(Un)trustworthy pledges and cooperation in social dilemmas - Goeschl, Timo; Soldà, Alice (AWI discussion paper series, 2023)
Pledges feature in international climate cooperation since the 2015 Paris Agreement. We explore how differences in pledgers' trustworthiness affect outcomes in a social dilemma that parallels climate change. In an online experiment, two participants interact with a randomly matched third player in a repeat maintenance game with a pledge stage. Treatments vary whether participants are matched with a player that is more or less trustworthy as revealed by behavior in a promise-keeping game; and whether they observe that trustworthiness. We find that participants knowingly matched with more trustworthy players cooperate more than participants matched with less trustworthy players (knowingly or unknowingly), but also more than participants unknowingly matched with more trustworthy players. In contrast, participants knowingly matched with less trustworthy players do not cooperate less than participants who are unknowingly so. Our findings suggest that the use of pledges, as per the Paris Agreement, can leverage the power of trustworthiness to enhance cooperation.
Keywords: Graue Literatur